2010
DOI: 10.1186/1471-2474-11-190
|View full text |Cite
|
Sign up to set email alerts
|

Staying at work with back pain: patients' experiences of work-related help received from GPs and other clinicians. A qualitative study

Abstract: BackgroundLow back pain commonly affects work ability, but little is known about the work-related help and advice that patients receive from GPs and other clinicians. The purpose of this study was to explore the experiences of employed people with back pain and their perceptions of how GPs and other clinicians have addressed their work difficulties.MethodsA qualitative approach with thematic analysis was used. Individual interviews were carried out with twenty-five employed patients who had been referred for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 22 publications
1
59
0
Order By: Relevance
“…Although not exclusively so, this theme was particularly associated with studies that explicitly referred to a large proportion of participants still in paid employment (Coole, Drummond, & Watson, 2010;Coole, Watson, & Drummond, 2010a, 2010bHush et al, 2009;Liddle et al, 2007;May, 2001May, , 2007McPhillipsTangum et al, 1998;Strunin & Boden, 2004;Young et al, 2011).…”
Section: Listening and Communicationmentioning
confidence: 95%
See 1 more Smart Citation
“…Although not exclusively so, this theme was particularly associated with studies that explicitly referred to a large proportion of participants still in paid employment (Coole, Drummond, & Watson, 2010;Coole, Watson, & Drummond, 2010a, 2010bHush et al, 2009;Liddle et al, 2007;May, 2001May, , 2007McPhillipsTangum et al, 1998;Strunin & Boden, 2004;Young et al, 2011).…”
Section: Listening and Communicationmentioning
confidence: 95%
“…Care could be depersonalising rather than person-centred: 'you don't feel that you are being treated as a person at all' (Walker, Holloway, & Sofaer, 1999, p. 623). In particular, the typical GP was perceived as having limited resources and skills (Campbell & Guy, 2007;Chew & May, 1997;Coole, Watson, & Drummond, 2010a;Slade et al, 2009a). This description of the standard GP protocol for care 72 P. MacNeela et al…”
Section: Disappointment With Health Carementioning
confidence: 99%
“…#1 CINAHL heading terms and free text words related to work (MH "Work") or (MH "Occupations and Professions") or (MH "Employment+") or (MH "Absenteeism") or (MH "Sick Leave") or (MH "Occupational Health") OR TI ("sickness absence" OR "work status" OR "occupational status" OR "work ability" OR "work disability" OR "work attendance" OR "work performance" OR "occupationally active" OR "job retention" OR "work capacity" OR presenteeism OR "job status" OR "vocational status" OR "vocational rehabilitation" OR "employment status" OR occupation OR absenteeism OR employment OR "sick leave" OR "occupational health" OR "occupational ability" OR "stay at work" OR "return to work" OR "work participation") or AB ("sickness absence" OR "work status" OR "occupational status" OR "work ability" OR "work disability" OR "work attendance" OR "work performance" OR "occupationally active" OR "job retention" OR "work capacity" OR presenteeism OR "job status" OR "vocational status" OR "vocational rehabilitation" OR "employment status" OR occupation OR absenteeism OR employment OR "sick leave" OR "occupational health" OR "occupational ability" OR "stay at work" OR "return to work" OR "work participation") #2 CINAHL heading terms and free text words related to pain (MH "Chronic Pain") or (MH "Back Pain") or (MH "Neck Pain") or (MH "Shoulder Pain") or (MH "Pelvic Pain") or "widespread pain" OR "musculoskeletal pain" OR "work related pain") #3 #1 AND #2 #4 #3 AND Age Groups: Young Adulthood (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) MeSH descriptor Pain explode all trees #19 (#17 AND #18) #20 "sickness absence" OR "work status" OR "occupational status" OR "work ability" OR "work disability" OR "work attendance" OR "work performance" OR "occupationally active" OR "job retention" OR "work capacity" OR presenteeism OR "job status" OR "stay at work" OR "occupational ability" OR "vocational status" OR "vocational rehabilitation" OR "employment status" OR "return to work" OR "Work participation" OR "Occupation" OR "Absenteeism" OR "Employment" OR "Sick Leave" OR "Occupational Health":ti,ab,kw #21 "Back Pain" OR "Neck Pain" OR "Shoulder Pain" OR "Pelvic Pain" OR Fibromyalgia OR Whiplash OR Tendinopathy OR "Musculoskeletal pain" OR "Myofascial Pain" OR "Joint Instability" OR "Cumulative Trauma Disorder" OR "repetitive strain injury" OR (complaints AND (arm OR neck OR shoulder)) OR "chronic pain" OR "widespread pain" OR "work related pain":ti,ab,kw #22 (#1 OR #2 OR #3 OR #4 OR #5 OR #6 OR #7 OR #8 OR #9 OR #10 OR #19 OR #21) #23 (#11OR #12 OR #13 OR #14 OR #15 OR #16 OR #20) #24 (#22 AND #23) Box 1. Criteria for assigning grade of evidence.…”
Section: Search History Cinahlmentioning
confidence: 99%
“…Several terms are used for working with pain, such as staying at work (SAW) [26,27], remaining or continuing a work role [28], working despite pain [29][30][31], continuing work with pain [32,33], remaining in employment [34], work maintenance [35], staying on the job [36], retaining work [26] and keeping on working [37]. For the purpose of this review, SAW was defined as sustained work participation despite CMP for at least 1 year, without present sick leave due to CMP.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] Studies have concluded that there is a need for more information about how and why sickness certification is problematic and how to improve the process. 12,25,26 The primary goal of this study is to address this gap in knowledge, and gain an insight into how the new fit note might be used to improve sickness certification for the chronic pain patient.…”
mentioning
confidence: 99%